2020
DOI: 10.1101/2020.07.30.228908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel mechanistic insights into the role of Mer2 as the keystone of meiotic DNA break formation

Abstract: One of the defining features of sexual reproduction is the recombination events that take place during meiosis I. Recombination is both evolutionarily advantageous, but also mechanistically necessary to form the crossovers that link homologous chromosomes. Meiotic recombination is initiated through the placement of programmed double-strand DNA breaks (DSBs) mediated by the protein Spo11. The timing, number, and physical placement of DSBs are carefully controlled through a variety of protein machinery. Previous… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…Hop1 and Red1 play a role in DSB formation by serving as a platform for the Mer2/Mei4/Rec114 DSB proteins ( Panizza et al, 2011 ; Figure 2 ) that then promote Spo11 catalytic activity through direct or indirect interactions with Spo11 ( Yadav and Claeys Bouuaert, 2021 ). This Hop1/Red1 function is mediated by the direct interaction between Hop1 and Mer2 in S. cerevisiae ( Rousova et al, 2020 ), and between their orthologs Hop1 and Rec15 in S. pombe ( Kariyazono et al, 2019 ). In the absence of Rec8, Hop1/Red1 and Rec114 still colocalize, but their positioning is altered ( Panizza et al, 2011 ).…”
Section: Organization Of the Chromosome Axial Element In S Cerevisiaementioning
confidence: 99%
See 1 more Smart Citation
“…Hop1 and Red1 play a role in DSB formation by serving as a platform for the Mer2/Mei4/Rec114 DSB proteins ( Panizza et al, 2011 ; Figure 2 ) that then promote Spo11 catalytic activity through direct or indirect interactions with Spo11 ( Yadav and Claeys Bouuaert, 2021 ). This Hop1/Red1 function is mediated by the direct interaction between Hop1 and Mer2 in S. cerevisiae ( Rousova et al, 2020 ), and between their orthologs Hop1 and Rec15 in S. pombe ( Kariyazono et al, 2019 ). In the absence of Rec8, Hop1/Red1 and Rec114 still colocalize, but their positioning is altered ( Panizza et al, 2011 ).…”
Section: Organization Of the Chromosome Axial Element In S Cerevisiaementioning
confidence: 99%
“…Thus, the potential DSB sites, which are promoter regions and have accessible chromatin, are brought, or stabilized to the axis thanks to the partly characterized interactions of H3K4me3 with Spp1 and of Spp1 with Mer2 ( Acquaviva et al, 2013 ; Sommermeyer et al, 2013 ; Adam et al, 2018 ). How the RMM complex is localized remains to be understood and the interaction detected between HORMAD1 and IHO1 ( Stanzione et al, 2016 ) and between Hop1 and Mer2 ( Rousova et al, 2020 ) is one determinant for this localization.…”
Section: Functional Roles Of the Meiotic Axis Organization In Early Meiotic Prophase Imentioning
confidence: 99%
“…A recent study independently reported phase separation by Mer2 and its mouse homolog IHO1 ( Tsai et al, 2020 ). In addition, Mer2 was shown to bind directly to histone octamers, suggesting the possibility that the condensates may involve chromatinized templates, not only naked DNA ( Rousova et al, 2020 ).…”
Section: Organization Of the Meiotic Dsb Machinerymentioning
confidence: 99%
“…8). Chromosome-associated proteins of interest also include Spp1, which recognizes molecular modifications on histone proteins bound to hotspot DNA, and might recruit these sequences to RMM condensates for breakage [8][9][10] .…”
Section: Kevin D Corbettmentioning
confidence: 99%